Analysis of Oil Palm Marketing Efficiency in Tommo District, Mamuju, Indonesia - Supardi Hasanuddin (Golden Ratio of Marketing and Applied Psychology of Business, 2021)
This study aims to determine the pattern of oil palm marketing channels, the number of costs and marketing margins obtained by each marketing agency, as well as the efficiency of oil palm marketing channels. The respondents were 34 information, consisting of 30 oil palm farmers and traders collecting oil palm FFB in Tommo District. Marketing of oil palm FFB is carried out using the snowball sampling method. The results of this study indicate that there are three marketing channels formed. Namely: Marketing channel I, namely Farmers sell directly to palm oil mills, Marketing channel II, namely sales through farmer groups then sold to palm oil mills, Marketing Channel III, namely Farmers selling to collector traders then sold to palm oil mills, highest marketing costs is in the channel I. The costs incurred in this marketing channel are transportation costs of Rp. 11.36/Kg of FFB, labor costs of Rp. 21.88/Kg of FFB, retribution costs of Rp. 7.71/Kg of FFB. Marketing Channel shows that marketing channel I is an efficient channel. With a margin value of 4.07 percent and a farmer's share of 95.92 percent, the production volume is 32.78 tons or 24.45 percent. Farmer share for the selling price of FFB is the highest farmer share because farmers directly sell their harvest to the factory.